Temperature preference by bats in the montane forests of Machu Picchu, Peru - Arias, Sandra (2020)
Information on the thermal preference of bats goes back to studies carried out since the middle of the 20th century, mainly in NorthAmerica and Europe. Here we present information on the thermal preference of six bat species in the cloud forests of the HistoricSanctuary of Machu Picchu (Cusco, Peru). The data were obtained in field using a thermographic camera and an infrared thermometer.Our results show the intervals and averages of the selected temperatures, as well as the differences between sexes of each species. Thisinformation constitutes the first effort in Peru to understand the temperature ranges that natural and artificial bat refuges should have.